Parâmetros seminais e composição bioquímicas do plasma seminal de coelhos criados no nordeste do Brasil - Alencar, Jôsy Maria Arruda de (2011)
This study was carried out to characterize the biochemical composition of seminal plasma and semen parameters of rabbits reared in Northeast Brazil, also identifying the changes that occur throughout the year. The experiment was conducted at the Sector of the Rabbit Department of Animal Science / UFC. The index of thermal comfort inside the facility was constructed according to the formula of the THI, modified for rabbits. The ejaculates were obtained twice a week from 20 New Zealand White rabbits, reared in flat-deck system (October/2009 to September/2010). After collection, the semen was measured and evaluated for volume, color, appearance, vigor, sperm concentration and motility. To obtain the SP, the semen was centrifuged and then stored at - 18°C. To perform the biochemical analysis was made a monthly pool of PS of each animal. The samples were tested according to the concentrations of fructose, glucose, total cholesterol and total protein. In this study, semen parameters were affected significantly (p <0.05) by sampling month, despite the presence of heat stress. In the evaluation of semen parameters was found that the color of the ejaculates was pearly white representative of good semen quality. Regarding the aspect, the best results were found in ejaculates with cream-milky appearance. With regard to biochemical characteristics, the aspect of the ejaculate significantly (p <0.05) only the concentrations of fructose and glucose. Significant differences in concentrations of fructose among the different months of the year. Glucose was identified as a constituent, usually found in the PS. Significant differences in concentrations of fructose among the different months of the year. Glucose was identified as a constituent, usually found in the PS. The study of the Pearson correlations showed significant associations (low and moderate) positive and negative differences between the semen parameters and biochemical. In this study we found a negative correlation with sperm concentration of fructose. The results showed that rabbits show created in Northeastern Brazil are perfectly adapted, as seminal and biochemical characteristics have normal, despite the existence of heat stress.